Electrochemistry and first principles of quantum mechanics - Bueno, Paulo Roberto [UNESP] (My University, 2018)
In Chap. 1, we demonstrated that nanoscale electronics and electrochemistry both originate from the same physical background and are underpinned by chemical capacitance and its association with quantised relaxation resistance, thus defining the timescale of electronic processes that occur at the molecular scale.